Muhammadiyah Goes International? Challenges and Opportunities - Putri Shafarina Thahir (Universitas Muhammadiyah Malang, 2024)
The idea of Muhammadiyah internationalization emerged as a response to the phenomenon of globalization, where Muhammadiyah tried to ensure that its da'wah movement was in line with the conditions of the times. This approach also includes global social issues such as the fate of workers, gender inequality, nuclear issues, and the environment. Muhammadiyah has a high commitment to the values of Pancasila and tries to contribute to achieving Indonesia's national ideals as stated in the Preamble to the 1945 Constitution. In the international context, Muhammadiyah not only plays a role as an Islamic movement but also as a socio-Islamic movement that tries to respond to various global issues. This article discusses how Muhammadiyah tries to develop the concept of peaceful Islamic da'wah amidst the complexity of the international world. Furthermore, it explains how Muhammadiyah's role in international relations involves active participation in conflict resolution, peacebuilding, and humanitarian activities in various countries. Muhammadiyah's internationalization strategy is explained through programs such as sending its best cadres abroad, establishing schools and charitable efforts in various countries, and participating in international forums. The author also discusses the concept of Muhammadiyah internationalization in three dimensions, namely ideas, roles, and movements. The idea of internationalization involves global socialization of the character of the Muhammadiyah movement and teachings. The role of internationalization includes increasing the role of Muhammadiyah in international forums, such as humanitarian missions, peace, and social activities. Meanwhile, the internationalization of the movement aims to make Muhammadiyah a model of Islamic practice that can be adopted globally. Furthermore, this article describes how Muhammadiyah, as an Islamic movement in Indonesia, is actively involved in the dynamics of the international world to encourage the transformation of the role of religions in overcoming global problems. Through internationalization, Muhammadiyah seeks to be part of a global movement that brings enlightenment, promotes Islam as a religion of peace, and contributes to the development of world civilization.